6(1+3m)=-9(-2m+5)-4

Simple and best practice solution for 6(1+3m)=-9(-2m+5)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(1+3m)=-9(-2m+5)-4 equation:


Simplifying
6(1 + 3m) = -9(-2m + 5) + -4
(1 * 6 + 3m * 6) = -9(-2m + 5) + -4
(6 + 18m) = -9(-2m + 5) + -4

Reorder the terms:
6 + 18m = -9(5 + -2m) + -4
6 + 18m = (5 * -9 + -2m * -9) + -4
6 + 18m = (-45 + 18m) + -4

Reorder the terms:
6 + 18m = -45 + -4 + 18m

Combine like terms: -45 + -4 = -49
6 + 18m = -49 + 18m

Add '-18m' to each side of the equation.
6 + 18m + -18m = -49 + 18m + -18m

Combine like terms: 18m + -18m = 0
6 + 0 = -49 + 18m + -18m
6 = -49 + 18m + -18m

Combine like terms: 18m + -18m = 0
6 = -49 + 0
6 = -49

Solving
6 = -49

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 11n=143 | | (-2/3)+8=(4/3)+6 | | -313/18=-3/2+2/3x | | (r^2)-7r-18=0 | | (-2/3x1)+8=(4/3x1)+6 | | 84/12=n | | 317/18=-1/2-5/3n | | -16=x+6 | | -7y-33=4y | | -53/12-8/12 | | 0.35/4.9x7=X | | 3(x+6)=x+2 | | -52/12-8/12 | | 4/7y+2/-8=-7 | | -4=3y-1+14 | | x^2+2x+(-3)=0 | | (2x-4)(2x+5)= | | 9.6=x/6 | | -5-(5y-1)=2(7y-16)-y | | 5z+32=4(2z+5) | | y/4-3=7 | | -8v-1=4v-1 | | w=1/4(x+y-z) | | -18-2x=36 | | 1/3x^2+4x-36 | | 3x(5y+38)(8x+26)= | | (6-16)/(2-7) | | 6-16/2-7 | | 3(2+x)=7 | | A+B=60B | | 40=-5n/8 | | p=(g-9)180forg |

Equations solver categories